Cell Type Dependent Suppression of Inflammatory Mediators by Myocardin Related Transcription Factors - Liu, Li; Bankell, Elisabeth; Rippe, Catarina; Morén, Björn; Stenkula, Karin G.; Nilsson, Bengt-Olof; Swärd, Karl (Frontiers in Physiology, 2021)
Myocardin related transcription factors (MRTFs: MYOCD/myocardin, MRTF-A, and MRTF-B) play a key role in smooth muscle cell differentiation by activating contractile genes. In atherosclerosis, MRTF levels change, and most notable is a fall of MYOCD. Previous work described anti-inflammatory properties of MRTF-A and MYOCD, occurring through RelA binding, suggesting that MYOCD reduction could contribute to vascular inflammation. Recent studies have muddled this picture showing that MRTFs may show both anti- and pro-inflammatory properties, but the basis of these discrepancies remain unclear. Moreover, the impact of MRTFs on inflammatory signaling pathways in tissues relevant to human arterial disease is uncertain. The current work aimed to address these issues. RNA-sequencing after forced expression of myocardin in human coronary artery smooth muscle cells (hCASMCs) showed reduction of pro-inflammatory transcripts, including CCL2, CXCL8, IL6, and IL1B. Side-by-side comparison of MYOCD, MRTF-A, and MRTF-B in hCASMCs, showed that the anti-inflammatory impact was shared among MRTFs. Correlation analyses using human arterial transcriptomic datasets revealed negative correlations between MYOCD, MRTFA, and SRF, on the one hand, and the inflammatory transcripts, on the other. A pro-inflammatory drive from lipopolysaccharide, did not change the size of the suppressive effect of MRTF-A in hCASMCs. To examine cell type-dependence, we compared the anti-inflammatory impact in hCASMCs, with that in human bladder SMCs, in endothelial cells, and in monocytes (THP-1 cells). Surprisingly, little anti-inflammatory activity was seen in endothelial cells and monocytes, and in bladder SMCs, MRTF-A was pro-inflammatory. CXCL8, IL6, and IL1B were increased by the MRTF-SRF inhibitor CCG-1423 and by MRTF-A silencing in hCASMCs, but depolymerization of actin, known to inhibit MRTF activity, had no stimulatory effect, an exception being IL1B. Co-immunoprecipitation supported binding of MRTF-A to RelA, supporting sequestration of this important pro-inflammatory mediator as a mechanism. Dexamethasone treatment and silencing of RelA (by 76±1%) however only eliminated a fraction of the MRTF-A effect (≈25%), suggesting mechanisms beyond RelA binding. Indeed, SRF silencing suggested that MRTF-A suppression of IL1B and CXCL8 depends on SRF. This work thus supports an anti-inflammatory impact of MRTF-SRF signaling in hCASMCs and in intact human arteries, but not in several other cell types.